The practice of government public relations - Lee, Mordecai, 1948-; Neeley, Grant; Stewart, Kendra B. (Public administration and public policy., 2022)
"Along with such traditional management tools as budgeting, HR, planning and leadership, The Practice of Government Public Relations, Second Edition demonstrates that the 21st century government administrator needs new tools to address the changing context of government communication. It provides public managers with an understanding of the uses of public relations as tools to advance the goals of public agencies, including media relations, contributing to an informed public, public branding, listening to the citizenry, and crisis management. While no manager can be an expert in all aspects of public administration, this book will help managers know what external communications tools are available to them for advancing the mission and results of their agencies. The authors argue that government public relations activities can serve three broad purposes: mandatory activities, which support governance; optional activities, which offer a pragmatic means of improving policy outcomes, inputs, and impacts; and dangerous but powerful activities, which may serve political interests. The book focuses on practitioners throughout the public sector, including the US federal government, state and local governments, and public administrators outside of the US. Several new chapters address the use of digital communications as social media and the resultant rapid diffusion of information has transformed the responsibility, accessibility, and vulnerability of government communications. In addition, two new chapters examine the topic of branding, its growing influence in the public sector, and how it can be used to connect with citizens and increase public engagement. The Practice of Government Public Relations, Second Edition is designed to help government managers are various levels of administration looking to specialize in public relations, those assigned to communications offices, and program managers seeking innovative and cost-effective ways to implement their programmatic missions. It will also be of interest to students of publication administration who will become the government workers of the future"--